2012
DOI: 10.1007/s13770-012-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural differentiation of rat muscle-derived stem cells in the presence of valproic acid: A preliminary study

Abstract: In this study, we chose valproic acid (VA) for inducing neural differentiation in rat muscle-derived stem cells (rMDSCs). After pre-induction with basic fibroblast growth factor (bFGF) and subsequent treatment with VA, VA-related cytotoxicity to rMDSCs was relatively low. In addition, VA-treated rMDSCs exhibited a neural-like morphology after 1, 4, and 7 days. The immunocytochemical results of VA-treated rMDSCs showed abundant cells stained positive for neuron-specific enolase (NSE) and neuron filament (NF) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our previous data indicated that higher concentrations (4 mM) resulted in considerable cell death, and the cytotoxicity induced by VA appeared to be dose-dependent [18]. Thus, VA at a concentration of 1 mM, which was only slightly toxic, was selected to represent a differentiation of rMDSCs in the subsequent experiments in this work.…”
Section: Attachment Of Rmdscs To Chitosan Hydrogel In Vitromentioning
confidence: 95%
See 2 more Smart Citations
“…Our previous data indicated that higher concentrations (4 mM) resulted in considerable cell death, and the cytotoxicity induced by VA appeared to be dose-dependent [18]. Thus, VA at a concentration of 1 mM, which was only slightly toxic, was selected to represent a differentiation of rMDSCs in the subsequent experiments in this work.…”
Section: Attachment Of Rmdscs To Chitosan Hydrogel In Vitromentioning
confidence: 95%
“…VA-induction medium was prepared at 0 and 1 mM VA. Concentration dependence of VA in rMDSCs on TCP was performed in previous work [18]. Cytotoxicity was measured using a WST-1 kit (Roche, Germany) after 1, 4, and 7 days according to the manufacturer's instructions.…”
Section: Cytotoxicity Tests Of Rmdscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional linkage between skeletal muscle and the nervous system at neuromuscular junction is necessary for the normal function of various organs. Although a number of methods have been explored, muscle-derived stem cells can be induced to adopt neuronal lineages [148152]. Arsic et al reported that muscle-derived stem cells (skeletal muscle) began to express N-CAM, β -tubulin III, and GFAP [153].…”
Section: Transdifferentiation Of Muscle-derived Stem Cellsmentioning
confidence: 99%
“…One suggested disadvantage of ASCs is the limitation of the types of stem cells into which they can differentiate. However, this issue has also been overcome following recent studies demonstrating the potential of stem cell transdifferentiation to extraneous cells with their origin tissues [ 8 10 ]. The most commonly used ASCs for regenerative medicine are mesenchymal stem cells (MSCs), especially MSCs derived from bone marrow (BMSCs), because of their characteristics such as ease of isolation and fast proliferation in vitro .…”
Section: Introductionmentioning
confidence: 99%